"Home: home, sweet home or house prison?" a phenomenological perspective according to codependents of users of psychoactive substances (Research, Society and Development, 2021)
The objective was to reflect on the home environment of codependents as an environment of coexistence with addicts of psychoactive substances in a phenomenological perspective. Descriptive investigation, outlined in the phenomenological approach in the light of Michel Maffesoli's theoretical-methodological-philosophical framework, carried out in a Basic Health Unit in Minas Gerais, Brazil, with 08 codependents. Characterization data were collected and recorded individual in-depth interviews were conducted. Data treatment with phenomenological content analysis supported by SPSS software version 24 and NVivo Pro11. All ethical and legal aspects of research were met. The eight participants were 100% women. It was understood that this “home” can become a real “house arrest” when the everyday reality is marked by the multiple roles occupied by the participants who are managed together with the care of the chemical dependent family member. Stressful, painful situations that generate bad feelings such as fear, insecurity, sadness, and family conflicts must be the target of nursing care.